2019
DOI: 10.1016/j.molmet.2018.10.010
|View full text |Cite
|
Sign up to set email alerts
|

CPT1C in the ventromedial nucleus of the hypothalamus is necessary for brown fat thermogenesis activation in obesity

Abstract: ObjectiveCarnitine palmitoyltransferase 1C (CPT1C) is implicated in central regulation of energy homeostasis. Our aim was to investigate whether CPT1C in the ventromedial nucleus of the hypothalamus (VMH) is involved in the activation of brown adipose tissue (BAT) thermogenesis in the early stages of diet-induced obesity.MethodsCPT1C KO and wild type (WT) mice were exposed to short-term high-fat (HF) diet feeding or to intracerebroventricular leptin administration and BAT thermogenesis activation was evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 45 publications
(116 reference statements)
2
50
0
Order By: Relevance
“…Brown adipose tissue metabolic challenges such as HFD exposure and cold exposure are known to activate heat production by this tissue. Nonshivering thermogenesis triggering was prevented in Ucp1 knock‐out mice exposed to high‐fat diet, showing that it is crucial for the proper BAT response, and chronic HFD exposure was able to increase both Ucp1 and Pgc1α gene expression and UCP1 protein expression in mice . Even though pinealectomy did not alter that, we observed that melatonin therapeutic replacement further increased Ucp1 gene expression after acute high‐fat diet exposure, suggesting that melatonin acts on BAT preparation to this metabolic challenge.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Brown adipose tissue metabolic challenges such as HFD exposure and cold exposure are known to activate heat production by this tissue. Nonshivering thermogenesis triggering was prevented in Ucp1 knock‐out mice exposed to high‐fat diet, showing that it is crucial for the proper BAT response, and chronic HFD exposure was able to increase both Ucp1 and Pgc1α gene expression and UCP1 protein expression in mice . Even though pinealectomy did not alter that, we observed that melatonin therapeutic replacement further increased Ucp1 gene expression after acute high‐fat diet exposure, suggesting that melatonin acts on BAT preparation to this metabolic challenge.…”
Section: Discussionmentioning
confidence: 67%
“…The evidences of active interscapular brown adipose tissue (BAT) in adults reignited the interest of the scientific community, mainly for its nonshivering thermogenesis . Cold exposure and hypercaloric diets are well‐known BAT activators, as well as T4 after local conversion to T3 by iodothyronine deiodinase type II (Dio2), which seems to increase BAT thermogenic capacity and recruitment …”
Section: Introductionmentioning
confidence: 99%
“…Distinct neuronal circuits and signaling mechanisms within the brain, in particular, hypothalamus regulates energy balance (feeding and metabolism) through adjustments in physiological processes. Disruption of some of these hypothalamic mechanisms is thought to be involved in the obesity and had been targeted to improve energy balance homeostasis [7][8][9][10][11][12]. One such mechanism involves the melanocortin system.…”
Section: Introductionmentioning
confidence: 99%
“…One acknowledged explanation is that AMPK alters cellular lipid composition by regulating its downstream mediator carnitine palmitoyltransferase 1 (CPT-1), resulting in elevated intracellular ceramide contents, which cause lipotoxicity and trigger the initiation of ER stress (52). In line with this observation, mice lacking CPT-1C display higher hypothalamic ER stress levels and body weight as well as impaired thermogenic response to shortterm HFD exposure (145). Given the fact that THs, GLP-1, E2, BMP8B and leptin all stimulate BAT thermogenesis by inhibiting AMPK within the VMH and the close relationship between hypothalamic AMPK and ER stress (16,52,64,66,114), the VMH AMPK-ER stress-BAT axis may represent a canonical pathway for multiple peripheral signals that act on the VMH to control thermogenesis, although more studies are needed to further testify this hypothesis.…”
Section: Er Stress In the Vmh: Linking Ampk To Thermogenesis?mentioning
confidence: 99%